2015
DOI: 10.1155/2015/971059
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Disposable Streamlined Liner of the Pharynx Airway and the Disposable I-gel in Anaesthetized, Paralyzed Adults: A Randomized Prospective Study

Abstract: Introduction. This study compared streamlined liner of the pharynx airway (SLIPA) and I-gel noninflatable, single-use, supraglottic airway device (SAD) performance in anesthetized, paralyzed adults. Methods. Eighty adults (ASA physical statuses I–III) who were undergoing elective procedures under general anesthesia with an SAD were enrolled in this prospective, randomized, single-blind study. Subjects were randomly and evenly assigned to the SLIPA or I-gel group for intraoperative airway management. Ease and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 52 publications
1
6
1
Order By: Relevance
“…Consistent with our hypothesis, the insertion success rate was significantly higher using the modified device compared to the unmodified device, indicating that the 120° bend facilitated successful SLIPA insertion by novice doctors. Previous studies have reported higher success rates with the conventional method than those obtained in our study, but they focused on adults and some were performed by experienced doctors , the success rate for SLIPA insertion into children using a device bent by 150° was 96%, but in that study, all insertion were performed by one experienced doctor.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Consistent with our hypothesis, the insertion success rate was significantly higher using the modified device compared to the unmodified device, indicating that the 120° bend facilitated successful SLIPA insertion by novice doctors. Previous studies have reported higher success rates with the conventional method than those obtained in our study, but they focused on adults and some were performed by experienced doctors , the success rate for SLIPA insertion into children using a device bent by 150° was 96%, but in that study, all insertion were performed by one experienced doctor.…”
Section: Discussioncontrasting
confidence: 73%
“…Zhu et al reported an 18% incidence of blood stains on SLIPA after removal for a SLIPA bent 150°. In studies using an unmodified device, the blood stains on SLIPA after removal incidence ranged from 5.0 to 41.4% in adults . The low incidences of complications were mainly attributed to that each novice had only one chance to insert the device into a patient in our study, whereas a forementioned studies have allowed three insertion attempts.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The ease of SAD insertion was qualitatively evaluated using the following 4-point scale [5,12]. A score 1 means easy insertion on first attempt with no need for adjustment, a score 2 is considered in case of slight difficult insertion on first attempt with at least one adjustment maneuver.…”
Section: Surgical Procedures and Clinical Observationsmentioning
confidence: 99%
“…The Oropharyngeal sealing pressure (OSP) was measured once an effective airway had been achieved using a fresh gas flow rate of 5 L/min, closure of the adjustable pressure limiting valve of the anesthetic circuit and recording the pressure when gas was heard leaking around the device [5,13]. Sore throat also was assessed as present or absent one hour after the operation and the patient was asked about the presence of dysphonia one hour and 24 hours postoperative.…”
Section: Surgical Procedures and Clinical Observationsmentioning
confidence: 99%